Perpanjangan Lintas Dan Rencana Pola Operasi Kereta Api Lembah Anai Wilayah Divre II Sumatera Barat - Eka Arista Anggorowati; Anggun Mega Nurfadhilla; Ari Widi Wibowo; Enrico Pria Anggana (Jurnal Penelitian Transportasi Darat, 2021)
ABSTRACTThe growing population and the shifting of population movement from the suburbs to the city center will make the demand for rail transportation services to the city center increase. To deal with this problem, it is necessary to study the analysis related to potential demand, the need for the number of facilities and new operating patterns for the extension of railroad relations. The results of the research showed that the potential demand was obtained from the calculation of actual and potential demand, where the actual demand was obtained by carrying out a survey on train from 644 respondents, 85.5% agreed with the extension of the Lembah Anai Railway relation and as many as 88% were willing to choose the train mode. In the potential demand analysis, a stated preference survey was carried out in Pauh District, from 2636 respondents, 86.7% were willing to switch from private vehicles and public transportation to the railroad mode. Based on the analysis of the calculation of facility requirements according to the demand, 1 trainset is ready for operation to accommodate the community to carry out daily mobilization to the center of the Central Business District (CBD) in Padang City.Keywords: Demand, pattern of rail operations, Railway Travel Graph (RTG) ABSTRAK Berkembangnya jumlah penduduk dan semakin bergesernya pergerakan penduduk dari pinggiran kota menuju pusat kota akan membuat semakin meningkatnya jumlah permintaan akan jasa angkutan kereta api sampai menuju pusat kota. Untuk menunjang permasalahan tersebut perlu dikaji analisis terkait potensi demand, kebutuhan jumlah sarana dan pola operasi baru perpanjangan relasi kereta api. Hasil penelitian menunjukkan potensi demand didapatkan dari perhitungan demand aktual dan potensial, dimana demand aktual dilakukan survey on train dari 644 responden 85,5% setuju dengan adanya perpanjangan relasi Kereta Api Lembah Anai dan sebanyak 88% bersedia untuk memilih moda kereta api. Pada analisis demand secara potensial dilakukan survey stated preference di Kecamatan Pauh dari 2636 responden 86,7% bersedia untuk pindah dari moda kendaraan pribadi dan angkutan umum ke moda kereta api. Berdasarkan analisis perhitungan kebutuhan sarana sesuai dengan demand didapatkan 1 trainset Siap Operasi untuk mengakomodir masyarakat melakukan mobilisasi sehari-hari menuju pusat Central Business District (CBD) di Kota Padang.Kata kunci : Demand, kebutuhan sarana, pola operasi kereta api, Grafik Perjalanan Kereta Api (Gapeka)